Environmental risk communication : principles and practices for industry - Sadar, Anthony J.; Forney, Susan Zummo (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
"Modern industry faces many communication challenges, including social media. This second edition is thoroughly updated, expanded, and reorganized to help industry communicators remain effective in addressing these new challenges. At the core of the book are foundational building blocks that address the human factors responsible for driving success or failure when communicating about environmental risk. Coupled with tools and best practices from decades of research, this insider's guide provides CEOs, plant managers, environmental compliance and health and safety officers, etc., with the direction and the confidence needed to prepare for difficult dialogue and high-pressure encounters"--
Revised edition of: Environmental risk communication / Anthony J. Sadar and Mark D. Shull. c2000.
OCLC-licensed vendor bibliographic record.
Keywords: Risk communication; Environmental management; SCIENCE / Environmental Science; BUSINESS & ECONOMICS / Business Communication / General